Exploring interference from analgesia in patients with cancer pain: a longitudinal qualitative study. Issue 13 (20th December 2013) - Manzano, Ana; Ziegler, Lucy; Bennett, Mike
<x xml:space="preserve">Abstract</x> Aims and objectives To increase understanding of the impact of analgesic side effects in patients with cancer pain. Background Studies in the area of cancer pain often refer to the need to find a satisfactory balance between analgesics and side effects as the key to cancer pain management. We explore how patients achieve this balance, its components and how it affects pain treatment adherence. Design An exploratory longitudinal study using qualitative research methodology. Methods Twenty‐five semi‐structured face‐to‐face interviews with patients with advanced cancer and their caregivers. Longitudinal interviews were conducted with patients (n = 11) at six‐week intervals over three months. Eleven first interviews, eight second interviews and six third interviews were completed with attrition due to death or ill health. Ten of the 25 interviews included caregivers. Results How cancer pain analgesics interfere with patients' life determines their adherence to the prescribed treatment. Compromises were made to manage three elements: pain, cognitive adverse effects of analgesics and physical activity. Negotiations and choices within this triad fluctuated and were determined by multiple psychosocial circumstances affecting patients and their caregivers varying from simple to complex. Patients with cancer and their caregivers actively managed the interference of analgesic drugs in their cognitive abilities and displayed a variety of nonadherence behaviours. Conclusion Further understanding of the role of analgesic side effects in the success of cancer pain management in patients is needed. This would enable clinicians to frame an optimal pain management plan. Relevance to clinical practice Clinicians should advise their patients about side effects of analgesic drugs, specifically the impact that cognitive alterations might have on their lives and subsequent adherence behaviour. Helping patients to achieve a balance between pain, adverse effects and physical function should have a key place in pain management strategies with advanced cancer.